Inflammatory factors and risk of meningiomas: a bidirectional mendelian-randomization study - Zhang, Zhiyun; Wang, Shengnan; Ren, Fei; Yang, Laiyu; Xie, Haoqun; Pan, Lin; Li, Yifan; Yu, Bingcheng; Yang, Yifan; Su, Haoyi; Chen, Youqi; Zhang, Chuyi; et al. (Frontiers in Neuroscience, 2023)
Background: Meningiomas are one of the most common intracranial tumors, and the current understanding of meningioma pathology is still incomplete. Inflammatory factors play an important role in the pathophysiology of meningioma, but the causal relationship between inflammatory factors and meningioma is still unclear. Method: Mendelian randomization (MR) is an effective statistical method for reducing bias based on whole genome sequencing data. It’s a simple but powerful framework, uses genetics to study aspects of human biology. Modern methods of MR make the process more robust by exploiting the many genetic variants that may exist for a given hypothesis. In this paper, MR is applied to understand the causal relationship between exposure and disease outcome. Results: Our results showed that higher tumor necrosis factor-beta (TNF-β) levels are linked to a higher incidence of meningiomas (OR=1.351, 95%CI=1.015-1.797, p=0.039). Furthermore, meningiomas predicted by genes have no effect on the expression of systemic inflammatory regulators. Conclusion: These findings suggest that TNF-β play a crucial part in the growth of meningiomas. Further research is needed to see if the biomarker can be utilized to prevent or treat meningiomas.